OSCE Insights 2021 Identifying Common Ground - Institute for Peace Research and Security Policy at the University of Hamburg / IFSH (Nomos Verlagsgesellschaft mbH & Co. KG, 2021)
The 2021 edition of OSCE Insights discusses the possibility of compromise among the 57 participating states of the OSCE. It includes a special issue that compares the interests of selected participating States in the OSCE and offers recommendations for bridging divisions within the organization.